The protective effect of Herba Cistanches on statin-induced myotoxicity in vitro. (22nd August 2016) - Wat, Elaine; Ng, Chun Fai; Koon, Chi Man; Wong, Eric Chun Wai; Tomlinson, Brian; Lau, Clara Bik San
Abstract: Ethnopharmacological relevance: Herba Cistanches (HC, Cistanche deserticola or Cistanche tubulosa ) is a Chinese herb traditionally used for muscle problems. Previous studies demonstrated that HC extract could reduce muscle damage and improve ATP storage in post-exercised rats. However, its effect on statin-induced muscle toxicity has never been investigated. Aim: The objective of this study was to determine if the aqueous extract of HC (HCE) could prevent simvastatin-induced toxicity in L6 rat skeletal muscle cells; and whether verbascoside is the major bioactive constituent which contributes to the effects. Materials and methods: MTT was performed to determine the effects of HCE (0–2000 µg/ml) or verbascoside (0–160 µM) on simvastatin (10 µM)-treated L6 cells. Annexin V-FITC/PI apoptosis assay and Caspase 3 assay were performed to determine the protective role of HCE on simvastatin-induced cell death, and to evaluate if HCE exerted its protective effect through the caspase pathway. ATP production was measured to investigate if HCE could prevent simvastatin-induced reduction in ATP production in vitro . Results: Simvastatin significantly increased apoptotic cell death in L6 cells. HCE significantly exerted a dose-dependent reduction on simvastatin-induced apoptotic cells, possibly via caspase-3 pathway. Simvastatin reduced the ATP production in L6 cells, which was dose-dependently prevented by HCE. There was only a trend but not significant effect (except at high dose) of verbascoside on the protection of simvastatin-induced muscle toxicity. Conclusions: In conclusion, we demonstrated for the first time that HCE could exert dose-dependent protective effect on simvastatin-induced toxicity in vitro, which was unlikely due to the presence of verbascoside. Our study suggested the potential use of HC under the situation of simvastatin-induced muscle toxicity. Graphical abstract: